CONTENT ANALYSIS AND VALIDATION METHODOLOGY FOR STRUCTURING AND IMPLEMENTING A STANDARD OPERATING PROCEDURE: EXPERIENCE REPORT - Victória Garbelini Ribeiro, Anna; David, Giovana; Freitas Baueb, Jorge; Bahov Shinnishi, Juliana; Moraes Armesto, Leonardo; Kawamoto DelaTorre, Lucas; Chaves Reis, Priscila; Roberto Alonso, Thabata (Revista Gênero e Interdisciplinaridade, 2023)
The study is developed in order to understand the methodological factors that best lead to the validation of a standardization instrument before a specialized technical body, according to the guideline suggested by Hoskins and criteria indicated by Lynn, in view of the opportunity of legitimation and formalization standard operating procedure (SOP) as a recognized and certified municipal tool. For this, the Standard Operating Procedure is given as an instrument that standardizes the follow-up, endorses the strengthening of the system-user bond and allows for improvements with regard to the degree of confidence of the information allocated in the patient registration system of the basic health units. health. This formalization attests to a milestone in the municipality, parameterizing its actions, further professionalizing its personnel, and guaranteeing the technical functionality relevant to each individual in primary care. The creation of the first municipal POP opens up a fertile and prosperous field for observation for the development of new procedures that contribute to more adequate lines of care, effectiveness in the service, guarantee of regularity in the use of resources, as well as in the assertive feedback of municipal data and referring to the direction of investment and intentionality of subsequent municipal health plans.